Specific Hemagglutinin and a Modulator of Complement in Cockroach Hemolymph - Anderson, Robert S. (1972)
Natural hemagglutinin activity against vertebrate erythrocytes is present in the hemolymph of the cockroach Blabarus craniifer. The hemagglutinin titer against rabbit erythrocytes is high, whereas sheep and horse red cells agglutinate weakly. Hemagglutinin activity was depressed by the complement inhibitor, cobra venom factor. Cockroach hemagglutinin is heat-labile; all activity is destroyed by heating at 56 C for 1 hr. A humoral factor similar to the complement component 3 proactivator is also present in cockroach hemolymph. The formation of the cobra venom factor-hemolymph “complex” is dependent on the presence of divalent cations and will not proceed at 56 C. The hemolytic intermediate formed after treatment of cockroach hemolymph with cobra venom factor was active in the presence of serum treated with ethylenediaminetetraacetic acid to inactivate the early complement components.